2022
DOI: 10.1097/ico.0000000000003167
|View full text |Cite
|
Sign up to set email alerts
|

Novel DCN Mutation in Armenian Family With Congenital Stromal Corneal Dystrophy

Abstract: Purpose: Congenital stromal corneal dystrophy (CSCD) is a rare congenital, dominantly inherited disorder characterized by diffuse stromal opacification associated with mutations in the decorin gene (DCN). As only 5 families with genetically confirmed CSCD have been reported, the identification of a novel pedigree provides the opportunity to better characterize the phenotype and genetic basis.Methods: An Armenian family with individuals in 4 consecutive generations demonstrated clinical features consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…CSCD is a very rare autosomal dominant inherited corneal dystrophy that has only been described in a few families. To our knowledge, this is the 10th reported 1,6–13 family, the seventh genetically 4,5,9–11,13 confirmed family and the first patient from Greece.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…CSCD is a very rare autosomal dominant inherited corneal dystrophy that has only been described in a few families. To our knowledge, this is the 10th reported 1,6–13 family, the seventh genetically 4,5,9–11,13 confirmed family and the first patient from Greece.…”
Section: Discussionmentioning
confidence: 77%
“…3,4 The disease is extremely rare because only 9 families have been described in the literature, of which 6 were genetically confirmed. 1,2,[5][6][7][8][9][10][11][12][13] In 2005, Bredrup et al 4 reported a frameshift mutation of the decorin (DCN) gene (c.967delT) on chromosome 12q21 leading to a C-terminal truncated protein. Decorin is a proteoglycan protein containing a single glycosaminoglycan side chain and a core protein consisting of leucine-rich repeats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, SPARCL1 stimulates decorin production (24). DCN is the established genetic cause of CSCD, with reports of cases with premature stop codons (5)(6)(7)(9)(10)(11)(12). Although CSCD typically presents with an onset in childhood, there is at least one report of the onset of the disease in adulthood, in which a novel missense DCN variant was identified (8).…”
Section: Discussionmentioning
confidence: 99%
“…Most corneal dystrophies are autosomal dominant, although autosomal recessive and X-linked corneal dystrophies have been described; however, the genetic basis for some presumed dystrophies remains unresolved (3). Congenital stromal corneal dystrophy (CSCD) is a rare autosomal dominant corneal dystrophy caused by variants in DCN (5)(6)(7)(8)(9)(10)(11)(12). Here, we describe the clinical features, histopathology, and genetic cause of a novel autosomal dominant stromal corneal dystrophy, which exhibits clinical similarities to CSCD and may share a common molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%